2023
DOI: 10.1101/2023.06.22.545931
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MX2 restricts HIV-1 and herpes simplex virus type 1 by forming cytoplasmic biomolecular condensates that mimic nuclear pore complexes

George D. Moschonas,
Louis Delhaye,
Robin Cooreman
et al.

Abstract: Human myxovirus resistance 2 (MX2) can potently restrict HIV-1 and herpesviruses at a post-entry step by a process that requires MX2 interaction with the capsids of these viruses. The involvement of other host cell factors in this process, however, remains poorly understood. Here, we mapped the proximity interactome of MX2 revealing strong enrichment of phenylalanine-glycine (FG)-rich proteins related to the nuclear pore complex as well as proteins that are part of cytoplasmic ribonucleoprotein granules. MX2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 122 publications
0
3
0
Order By: Relevance
“…The cognate-related human protein MxB is also cytoplasmic and shows antiviral activity against HIV and the herpes virus type 1 [11][12][13]17,22]. MxB, and GFP-MxB, also forms membraneless condensates on the cytosolic side of nuclear pores and thus inhibits the transit of viral RNA into nucleus [22,46] and citations therein. The major murine ortholog of both human MxA and human MxB genes is the murine Mx1 gene; the related protein is murine Mx1 [11][12][13]22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cognate-related human protein MxB is also cytoplasmic and shows antiviral activity against HIV and the herpes virus type 1 [11][12][13]17,22]. MxB, and GFP-MxB, also forms membraneless condensates on the cytosolic side of nuclear pores and thus inhibits the transit of viral RNA into nucleus [22,46] and citations therein. The major murine ortholog of both human MxA and human MxB genes is the murine Mx1 gene; the related protein is murine Mx1 [11][12][13]22].…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that nuclear murine GFP-Mx1 structures were also LLPS-driven biomolecular condensates which, like cytoplasmic human MxA condensates, disassembled in cells exposed to hypotonic ELB, and reassembled in cells then shifted to isotonic PBS [22]. Thus, not only did the subcellular localization of Mx family members contribute significantly to their respective antiviral spectrum, but also the cytoplasmic human MxB and nuclear murine Mx1 formed biomolecular condensates [22,46]. For our present discussion, we note that GTPase-null mutants of human MxA, which do not have antiviral activity, continue to form cytoplasmic condensates [11][12][13][14]44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Dimerization is required for MxB antiviral activity against HIV-1 ( 110 , 111 ). Recent experiments suggest that MxB may act as a decoy, luring HIV cores away from nuclear pores and thus impeding nuclear entry ( 112 ).…”
Section: Known Capsid-dependent Restriction Factorsmentioning
confidence: 99%